2018
DOI: 10.1038/s41419-018-0988-9
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer mesenchymal stem cells derived IL-8 induces PD-L1 expression in gastric cancer cells via STAT3/mTOR-c-Myc signal axis

Abstract: The expression of PD-L1 in tumor cells is one of the main causes of tumor immune escape. However, the exact mechanism for regulating PD-L1 expression in gastric cancer (GC) cells remains unclear. Our previous studies have shown that mesenchymal stem cells (MSCs) exert broad immunosuppressive potential, modulating the activity of cells either in innate or adaptive immune system to promote tumor progress. This study aims to investigate whether GCMSCs regulate the PD-L1 expression in GC cells and explore the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 35 publications
4
80
0
Order By: Relevance
“…Ehninger et al showed that, although HSCs express low levels of the cMYC protein, its expression increases steadily during progenitor differentiation [39]. A recent study showed that IL-8 activates mTOR and increases endogenous cMYC production, inducing PDL1 expression in gastric cancer [40]. In this study, IL-8 significantly increased not only the number of CD34+ cells but also that of CD34+/CD45-cells.…”
Section: Regarding the Role Of Cmyc In Hematopoiesis Wilson Et Al Rsupporting
confidence: 55%
“…Ehninger et al showed that, although HSCs express low levels of the cMYC protein, its expression increases steadily during progenitor differentiation [39]. A recent study showed that IL-8 activates mTOR and increases endogenous cMYC production, inducing PDL1 expression in gastric cancer [40]. In this study, IL-8 significantly increased not only the number of CD34+ cells but also that of CD34+/CD45-cells.…”
Section: Regarding the Role Of Cmyc In Hematopoiesis Wilson Et Al Rsupporting
confidence: 55%
“…To mobilize BMDC, TSF stimulates the bone marrow compartment, switching it from a quiescent state to a highly pro‐angiogenic and pro‐tumorigenic state. The expansion and mobilization of BMDC expressing immune checkpoint ligands could be key immunosuppressive mechanisms by which, disseminating tumor cells escape immune surveillance …”
Section: Bone Marrow‐derived Cellsmentioning
confidence: 99%
“…Similarly, microRNA-623 targeting of cyclin D1 also makes GC tumor cells more sensitive to 5-fluorouracil, thus improving the therapeutic effect of drugs [23]. GC mesenchymal stem cells can also promote the expression of PD-L1 through the STAT3/mTOR-c-Myc axis [24]. erefore, we performed western blot assays to observe the expression of cyclin D1 and c-MYC in different groups.…”
Section: Discussionmentioning
confidence: 99%